Odnos ciljeva postignuća, strategija učenja i ocjena u srednjoškolskoj nastavi fizike - Vrdoljak, Gabrijela (Array, 2018)
The aim of this paper was to examine relations between achievement goals, learning strategies and grades in high school physics class. Achievement goals represent an important motivational construct that has been developed within the theories of the self-regulatory learning and are connected to various educational outcomes, for instance, learning strategies and grades. The study was conducted on 208 second- and third-grade grammar school students. In order to examine the above-mentioned variables, the study used: Achievement Goal Questionnaire (Elliot & McGregor, 2001) which contains 12 items and measures four achievement goals: mastery approach, mastery avoidance, performance approach, and performance avoidance; Learning Strategies Scale (Lončarić, 2014) which contains 39 items and measures three learning strategy subscales: cycles of metacognitive control, deep cognitive processing, and surface cognitive processing. Class success criterion was previous year's physics grade. The relations between variables were verified by path analysis method. The study greatly confirmed anticipated relations (based on previous research). The achievement goals with approach tendencies have significantly positive effect on preferable educational outcomes. Achievement goals with avoidance tendencies are positively connected to surface processing. The results also confirmed the mediating effect of learning strategies in relation to mastery-approach goals and physics grades. This study emphasizes the necessity to direct students to learn in order to acquire the knowledge and competencies, and encourage the use of metacognitive strategies. This study, also, indicates some potential problems within the educational system (for instance, the absence of significant effect of the deep cognitive processing on the physics grades) which suggest the need for further research in this area.